البلاغة البصرية في الشعر الجزائري المعاصر - مسعي, نهاد (جامعة الوادي - university of Eloued, 2020)
عرفت القصيدة الجزائرية المعاصرة تغيرات في مسارها من البعد الانشادي إلى البعد البصري،انعكست على اشتغالها الفضائي المعتاد،متجاوزة بذلك الامتثال لاملاءات الأنساق الثابتة التي تنازع البقاء واختراق متراس النموذج الأبوي السائد الذي فرض وجوده وما يزال من قدسيات ذاكرة لا تقبل الخدش،ما أهل القصيدة إلى إعادة القولبة الوظيفية والشعرية والتداولية الطيعة من الوسائط المتغيرة لنحت نسقها الخاص بمقترحات الكتابة الأحدث المؤسسة على فاعلية البياض والسواد والترقيم والأشكال الهندسية واللوحات التشكيلية كبدائل تخفف الرسالة من الانهمام بوحداتها التركيبية لصالح لغة تداولية تواصلية،وتلزم المتلقي باستراتيجية خاصة لقراءة نص استثمر كل أبعاد التشكيل البصري عن طريق ادماج بنيات سيميوطيقية غير لغوية في بوليفونية جديدة تريد أن تستوعب الواقع الجديد.ولعل هذا ما تسعى إليه هذه الدراسة من خلال المقاربة النصية للكشف عن مواضع الازاحة البصرية في النصوص الشعرية الجزائرية المعاصرة. the contemporary algerian poem has changed its path from the assyrian dimension to the visual dimension , reflected in its usual space activity , surpassing the compliance with the dictates if the fixed patterns that survive and penetrate the podium of the dominant patriarcal model , which impised its existence and still is an undisputed memory .re- adapting the functional , poetic and délibérative functions of the changing media sculpt their own style of the latset writing proposals based on the effectiveness of whiteness, blakness, numbering , geomestric shapes and plastic painting as alternatives to reduce the a message from the intégration of its syntactic unites in favor of a communicative language .the récipient is obliged to have spécial strategy to read a text that has invested all the dimensions of the visual composition by incorporating semiotic linguistic structures into a new polyphony that wants to accommodate the new reality .perhaps this is what this study seeks through the textual approach to detect the places of visual displacement in contemporary algerian poetry texts.
مقال
Keywords: الشعر الجزائري المعاصر؛ الانزياح الكتابي؛ الشكل؛ التشكيل؛ الأساليب البصرية.; contemporary algerian poetry; biblical displacement; form; formation; visual méthodes.